Circularly polarized rectangular DRA coupled through orthogonal slot excited with microstrip circular ring feeding structure for Wi‐MAX applications. Issue 1 (3rd August 2017) - Kumar, Rajkishor; Chaudhary, Raghvendra Kumar
Abstract: In this article, a wideband circularly polarized rectangular dielectric resonator antenna (RDRA) coupled through orthogonal slots and excited with a new microstrip circular ring has been investigated. Circular polarization has been achieved by using plus shaped (+) slot on the ground plane and excited through a new microstrip circular ring feed. TE11 δ mode has been excited in the RDRA which has been confirmed through the distribution of E ‐field and dielectric waveguide model (DWM) method of RDRA. Circularly polarized (CP) RDRA offering measured −10 dB input impedance bandwidth of 20.79% (centered at 3.27 GHz) and 3 dB axial ratio bandwidth in broadside direction of 12.09% (centered at 3.39 GHz), respectively. From the CP radiation pattern, proposed design confirms that right‐ handed CP (RHCP) in broadside direction. The difference between RHCP field and left‐ handed CP (LHCP) field are above −26 dB in operational band. In addition, the proposed CP antenna offers stable gain and radiation efficiency in working bands and it is suitable for IEEE 802.16e/d Wi‐MAX (3.3‐3.7 GHz) band.